2019
DOI: 10.1001/jamasurg.2019.2879
|View full text |Cite
|
Sign up to set email alerts
|

Career Goals, Salary Expectations, and Salary Negotiation Among Male and Female General Surgery Residents

Abstract: In general surgery, women earn less money and hold fewer leadership positions compared with their male counterparts. OBJECTIVE To assess whether differences exist between the perspectives of male and female general surgery residents on future career goals, salary expectations, and salary negotiation that may contribute to disparity later in their careers. DESIGN, SETTING, AND PARTICIPANTS This study was based on an anonymous and voluntary survey sent to 19 US general surgery programs. A total of 606 categorica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 11 publications
2
34
0
1
Order By: Relevance
“…There were additional questions asked as a part of the survey that have already been reported elsewhere. 11 Survey questions were constructed as 4-point Likert scale, yes/no, true/false, or fill in the blank. Survey participants had the option of not responding to any question.…”
Section: Methodsmentioning
confidence: 99%
“…There were additional questions asked as a part of the survey that have already been reported elsewhere. 11 Survey questions were constructed as 4-point Likert scale, yes/no, true/false, or fill in the blank. Survey participants had the option of not responding to any question.…”
Section: Methodsmentioning
confidence: 99%
“…47,48 Men in leadership ben efit from the higher income associated with leadership and can also perpetuate the policies and informal support networks that recruit, retain and promote other men at disproportionately higher rates. 49,50 Women in medicine are more likely to experience imposter syndrome and to have lower salary expectations than men, 51 but this may result from the anchoring of expectations and feelings of selfworth that go along with lower starting salaries. 52 Likewise, women see themselves as less capable of negotiating higher pay than men 51 but are also more likely to experience consequences from trying to do so.…”
Section: What Are Some Of the Root Causes Of The Gender Pay Gap?mentioning
confidence: 99%
“…49,50 Women in medicine are more likely to experience imposter syndrome and to have lower salary expectations than men, 51 but this may result from the anchoring of expectations and feelings of selfworth that go along with lower starting salaries. 52 Likewise, women see themselves as less capable of negotiating higher pay than men 51 but are also more likely to experience consequences from trying to do so. 53 Biases in clinical care arrangements also lead to pay inequity.…”
Section: What Are Some Of the Root Causes Of The Gender Pay Gap?mentioning
confidence: 99%
“…Other researchers have suggested that complex systemic biases exist during training and in practice that contribute to the gender pay gap. 7,32,[46][47][48][49][50][51][52][53] The reasons underlying the discrepancy in payments that we observed are likely complex and multifactorial, and should be a focus of further research.…”
Section: Discussionmentioning
confidence: 70%